Intraperitoneal spread in uterine sarcoma following unprotected laparoscopic transvaginal uterine morcellation: a case report and literature review - Sun, Jianhao; Jiao, Xinjuan; Wu, Zhenzhen; Yao, Tingting; Tuo, Shumei; Wang, Yueyuan; Chen, Ruirong; He, Jing; Qian, Jifang; Xu, Shengfang; Liu, Qing (Frontiers in Oncology, 2024)
Clinically and through auxiliary examinations, distinguishing uterine leiomyoma from early-stage uterine sarcoma presents significant challenges. A 48-year-old patient underwent a laparoscopic hysterectomy for uterine leiomyoma, during which a large uterus was excised through the vagina and extracted. Four months post-operation, the patient developed abdominal distension, indicative of extensive pelvic-abdominal dissemination of uterine sarcoma. We hypothesize that unprotected fibroid fragmentation increases the risk of uterine sarcoma spread, thereby worsening the prognosis. Our literature review aims to thoroughly understand the risks associated with unprotected transvaginal laparoscopic tumor division.